Findings from transcriptomics and immunohistochemistry indicate an autoimmune disease targeting brainstem inhibitory interneurons in bovine spastic paresis. - Frederik Krull; Shahrbanou Hosseini; Martina Bleyer; Bertram Brenig (PLoS ONE)
Bovine spastic paresis (BSP) is a progressive neuromuscular disease of unknown origin that causes persistent stiffness of the hind limbs. The symptoms are similar to those of human motor neuron diseases such as primary (PLS) or amyotrophic lateral sclerosis (ALS). BSP occurs worldwide in cattle production with an estimated prevalence of <1%. For Germany, this means that around 20,000 Holstein cattle are affected. BSP is generally considered a hereditary disease, but there is no prevention through breeding programs. As a result, BSP not only affects animal welfare but also leads to economic losses in milk and beef production. Here, we used transcriptomics to analyse the brainstem, spinal cord and affected gastrocnemius muscle tissue of eight animals affected by BSP and eight control animals from slaughterhouses to gain new insights into the molecular mechanisms underlying BSP. We found that the expression of several genes was significantly different in animals affected by BSP compared to control animals. Specific genes for inhibitory neurons were downregulated in the brainstems of the affected animals, namely CCK (cholecystokinin), NPY (neuropeptide Y), and SST (somatostatin). These inhibitory neurotransmitters influence cerebral movement control, among other processes. Furthermore, OOSP2 (oocyte secreted protein 2) was found to be significantly upregulated in the affected animals in all tissues. This expression could best be explained by the presence of T-follicular-helper cells which, through interleukin 21, can trigger a TH-2-dominated immune response and lead to autoimmune encephalitis. Further cases were sampled for confirmation and we detected cell infiltrates of activated microglia and T-cells in the brainstem using immunohistochemistry. Microglial foci were significantly more abundant in animals affected by BSP than control animals. We conclude that BSP is caused by an autoimmune reaction directed against inhibitory interneurons in the brainstem and is due to a combination of genetics and environmental influences. This may result in lost controlling influence on the upper motor neurons via extrapyramidal pathways and therefore triggers the specific symptoms of motor neuron disease.